From BPS Guideline to BPS Directive: Has the Hospital Procurement Bar Moved? - John Beardwood (Healthcare Quarterly, 2011)
There have been an increasing number of concerns regarding procurement practices in the public sector, together with intensive media scrutiny of those practices in the health sector. Yet, notwithstanding those concerns, only Ontario and British Columbia have developed a comprehensive procurement framework to address these issues. (While a review of the British Columbia's procurement requirements is beyond the scope of this article, British Columbia's procurement manual is available electronically [BC Minister of Finance n.d.]. For more detailed information, please also see the BC Purchasing Handbook [BC Government 2010].) However, the way that the procurement regime in Ontario has developed has led to the potential for additional confusion in an area that is already complex, being based on the interaction of common law principles, trade agreements (e.g., the Agreement on Internal Trade) and governmental guidance (e.g., the Management Board of Cabinet procurement directive of July 2009). Specifically, the Ontario Ministry of Finance has issued and replaced in quick succession – over a two-year period – a series of documents seeking to provide guidance as to procurement practices. In April 2009, the Ministry of Finance issued the broader public sector (BPS) Supply Chain Guideline. (For a detailed review of guidelines, please see Understanding the PPP: The BPS Supply Chain Guideline [Beardwood 2010], which contrasts the procurement requirements under the guideline with annex 502.4 to the Agreement on Internal Trade and the Management Board of Cabinet procurement directive [July 2009] at: http://www.fasken.com/understanding-the-ppp/). However, notwithstanding that the guideline was issued in just 2009 and organizations were still in the process of understanding the implications of the guideline on their procurement practices, the guideline has now been replaced by the Broader Public Sector Procurement Directive (Ontario Ministry of Finance 2011), available as of February 1, 2011, on the Ministry of Finance website and effective on April 1, 2011, pursuant to the Broader Public Sector Accountability Act (Government of Ontario 2010).
Keywords: John Beardwood, Hospital procurement, public sector procurement, procurement framework